The safety and feasibility of transoral thyroidectomy vestibular approach in the treatment of thyroid disorders: An overview of systematic reviews - Huixia Ren; Mengyang Wang; Xuan Sun; Yin Yuan; Naijin Zhang; Ying Liu; Shujiao Yue; Yonghui Li; Yuanyuan Guan; Huaien Bu; Hongwu Wang (PLoS ONE, 2025)
Objective Many systematic reviews (SRs) and meta-analyses (MAs) have recently assessed the short-term outcomes of the transoral thyroidectomy vestibular approach (TOTVA) compared with conventional open thyroidectomy (COT) and non-transoral endoscopic thyroidectomy (NTET). However, their conclusions remain controversial. This overview aimed to evaluate the safety and feasibility of TOTVA by appraising the quality of existing SRs/MAs. Methods Seven Chinese and English databases were systematically searched from their inception to December 10, 2023. Eligible SRs/MAs, published between 2020 and 2023, compared the safety and efficacy of TOTVA with COT or NTET. The PRISMA, AMSTAR-2, and ROBIS tools were used to assess reporting quality, methodological quality, and risk of bias, respectively. Result Eleven SRs/MAs were finally included. According AMSTAR-2, one study was assessed as high-quality, with the remainder as very low-quality. Using PRISMA 2020, the “Yes” response rate for Q5, Q8, and Q15 was below 55 percent. Per ROBIS, all SRs/MAs exhibited low risk in phase 1 and domain 1 but high risk in domain 2. Efficacy was assessed through intraoperative outcomes, primary postoperative outcomes, and statistically significant postoperative outcomes. Patients with thyroid disorders undergoing TOTVA experienced longer overall operative time and hospital stays, reduced intraoperative blood loss, increased lymph node retrieval, higher incidence of infection, lower postoperative pain scores, reduced incidence of hypocalcemia, larger drainage volumes, and higher cosmetic effect scores compared with those undergoing. Conclusion The TOTVA may enhance cosmetic satisfaction, improve lymph node retrieval, and decreased postoperative complications. Nevertheless, these findings warrant cautious interpretation due to low methodological quality, high risk of bias, and limited evidence quality. More rigorous and standardized SRs/MAs are required to provide robust scientific evidence for definitive conclusions.